Married Women’s Knowledge, Attitude, and Practice Regarding Uterine Prolapse in Morang District of Nepal (Pragyaratna प्रज्ञारत्न, 2023)
Uterine prolapse is a common health problem, particularly among adults and old women in Nepal. This study aims to assess the level of knowledge on uterine prolapse among currently married women aged 15 to 49 years and assess their attitude and practice. Researchers used a descriptive research approach in this study. Participants were selected from simple random sampling, and the study area was selected from purposive sampling. There were 140 respondents aged 15 to 49 years currently married women. If there are two respondents in a single family, then the researcher has picked only one respondent for the interview. Semi-structured interview schedules have been used as a tool for the study. Research has identified various factors for uterine prolapse like age at first marriage, place of delivery, and history of abortion. Nearly one in two women had average knowledge of uterine prolapse, and one in four women had never heard of uterine prolapse. There are good practices (90 percent) for getting health facilities for uterine prolapse checkups. However, many of them are unaware of the Kegel exercise. Very few women (one in ten women) had a positive attitude towards uterine prolapse. To promote knowledge, attitudes, and practices of uterine prolapse, health promotion programs should target women from all caste/ethnic groups, age groups, and education levels, including urban and rural communities.